1993
DOI: 10.1002/bit.260410305
|View full text |Cite
|
Sign up to set email alerts
|

Relieving effects of glycine and methionine from acetic acid inhibition in Escherichia coli fermentation

Abstract: Among amino acids screened for their potential to relieve wild and recombinant Escherichia coli from the negative effects of acetic acid, glycine, and methionine showed a sparing effect. In the presence of 2 g/L of acetic acid, addition of 0.5 g/L of glycine or methionine resulted in either a complete recovery or a further enhancement in the specific growth rate, while the enhancement was significant but not fully complete in the presence of 4 g/L of acetic acid. The addition of 0.5 g/L of methionine alleviate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 23 publications
1
30
1
Order By: Relevance
“…Here we have confirmed the findings of an earlier study by Han et al (1993), which showed that methionine could relieve the acetate-mediated inhibition of growth of an E. coli culture. We have shown that the effects of methionine on acetate-mediated inhibition of growth can be replicated for other organic acids.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Here we have confirmed the findings of an earlier study by Han et al (1993), which showed that methionine could relieve the acetate-mediated inhibition of growth of an E. coli culture. We have shown that the effects of methionine on acetate-mediated inhibition of growth can be replicated for other organic acids.…”
Section: Discussionsupporting
confidence: 92%
“…Methionine stimulated the growth rate of cells treated with up to 20 mM acetate at pH 6 (data not shown). In the earlier study (Han et al, 1993), glycine was also found to relieve growth inhibition, but we were unable to observe growth stimulation by this amino acid in E. coli Frag1 (data not shown).…”
Section: Inhibition Of Growth By Weak Organic Acids Is Reversed By Mecontrasting
confidence: 56%
See 2 more Smart Citations
“…Finally, genes in a putative operon orthologous to microbial methionine transporters (CAC0984-CAC0986) were differentially upregulated after acetate stress. Studies in E. coli have shown that acetate inhibition at 8-33 mM concentration can be relieved by the addition of methionine (Han et al, 1993;Roe et al, 2002). A result of acetate stress is accumulation of the toxic intermediate homocysteine (Roe et al, 2002).…”
Section: Differential Expression Of Amino Acid Biosynthesis and Transmentioning
confidence: 99%